H1N1V influenza in pregnancy in the UK. (16th November 2010) - Pierce, M; Kurinczuk, JJ; Spark, P; Brocklehurst, P; Knight, M
Abstract : Background: Pregnant women are known to be at higher risk of complications of seasonal flu. Early reports in the H1N1v influenza ('swine flu') pandemic suggested that these risks may be particularly high with this strain of the disease. UK-wide surveillance of women hospitalised with H1N1v infection during pregnancy was therefore commenced in order to describe management and outcomes and inform ongoing clinical guidance. Methods: A national case-control study was conducted using the UK Obstetric Surveillance System collaborating clinicians to identify women hospitalised with H1N1v influenza between September 2009 and January 2010. Results: 169 pregnant women were admitted to hospital with laboratory confirmed H1N1v infection. Women hospitalised with H1N1v in pregnancy more likely to be aged less than 20 (OR 1.9, 95% CI 1.1 to 3.3), obese (OR 2.0, 95% CI 1.3 to 3.1); multiparous (OR 1.5, 95% CI 1.0 to 2.1) and asthmatic (OR 3.2, 95% CI 2.0 to 5.2) than control women. 65% of women were managed initially with zanamivir; 13% of these were later switched to oseltamivir. 46% of women were treated with antivirals within 2 days of symptom onset; only 9% had been treated before hospital admission. Women not treated with antivirals within 2 days were more likely to be admitted to ITU (OR 3.1, 95% CI 1.2 to 7.9) and women who were admitted to ITU were more likely to deliver preterm (OR 15.1, 95% CI 3.7 to 60.8). Conclusion: This study demonstrates the importance of early treatment with antivirals in improving maternal outcomes of H1N1v infection. Follow-up of women with ongoing pregnancies is required to fully document the impact on pregnancy outcomes.